DARI KARTINI HINGGA AYU UTAMI: MEMPOSISIKAN PENULIS PEREMPUAN DALAM SEJARAH SASTRA INDONESIA - -, Nurhadi (Diksi, 2015)
There has been an interesting phenomenon beginning late in the 20 st century and lasting until early in the 21 century in Indonesian literary history: the great number of women writers suddenly producing literary works. In denial of the idea that it has been a phenomenon occurring all of a sudden, there has been a precedent that could not be ignored: the number of Indonesian women writers coming into activity far before the 1920s, the period becoming a milestone marking the start of modern Indonesian literature, itself resulting from an impact of Western acculturation. The impact appeared first in the person named Kartini, a woman writer of some renown, whose achievement in the literary world is often unmentioned. The absence of women writers in the past from lists of known writers was often related to activities of placing their role on the sidelines by, for example, not categorizing them writers of literary works or writers of quality literature (they being considered merely writers of popular literature) or categorizing them merely happy-go-lucky writers and not the main representatives of their generation of writers. One may wonder whether the recent acknowledgement of Ayu Utami in Angkatan 2000 Sastra Indonesia as a pioneer in novel writing has been one of the strategies to bring about something contrary to what has happened to those women writers in the past. It seems that the recent emergence of the aforementioned great number of women writers has not been automatically related to the efforts made by the feminist movement. A writer who has made efforts for the sake of Kartini’s fate is a male writer: Pramudya Ananta Toer. Keywords : women writers, feminism, Indonesian literary history, role of historical writing